Spatial usage in the royal and commoner residences in Kuala Kangsar: a compatibility analysis to the Islamic guidelines and custom manifestations - Abdul Majid, Noor Hanita; Denan, Zuraini (IIUM Press, 2014)
The relationship between Islamic guidelines and Malay culture to traditional Malay architecture has been an accepted fact. Nevertheless, the factors that influence culture such as customs have been testified to have inconsistencies with Islamic guidelines. It is hypothesized that the Malays Muslims in Malaysia practices the Malay custom or Adat that in turn has affected the spatial usage in the traditional dwelling architecture; may it be the royal or commoners residences. This paper identifies the Islamic guidelines and customs related to wedding ceremonies and analyzes the spatial usage and activities conducted. The comparison between royal and commoners residences indicates that the residential layout differs in terms of the complexity of customs practiced at the selected case studies. The case studies chosen for the spatial studies are the Bytul Anwar and Baitul Rahmah representing the royal residences and Rumah Meor representing the commoner’s residences. Generally, there are similarities in terms of layout and hierarchy of the spaces involved in conducting the ceremonies. There are also evidences that Islamic guidelines has been absorbed in the customs practiced during wedding ceremonies with additions and modifications in the royal and commoners practice. The results suggested there are strong custom manifestations in the spatial usage at both royal and commoners’ residences.